2021
DOI: 10.3390/foods10030604
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Mitigation of Acrylamide, 5-Hydroxymethylfurfural, and Oil Content in Fried Dough Twist via Different Ingredients Combination and Infrared-Assisted Deep-Frying

Abstract: The effect of main ingredients (wheat flours, polyol sweeteners, and frying oil) and infrared-assisted deep-frying on the acrylamide, 5-hydroxymethylfurfural (HMF), oil content, and physicochemical characteristics of fried dough twist (FDT) were investigated. The amount of acrylamide and HMF produced in FDT made with low-gluten flour is significantly lower than that of flour with high gluten content. Among polyol sweeteners, maltitol causes the greatest reduction in acrylamide and HMF in FDT. Moreover, the oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Furthermore, the use of IF application had a remarkable influence on altering the physical and chemical properties of related product, leading to enhanced functionality (Juodeikiene et al., 2018). As such in Ates and Unal's paper (2023), gluten amount may probably have direct proportion with acrylamide quantity (Han et al., 2021). Because Han et al.…”
Section: Technologies For Reduction Of Acrylamidementioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, the use of IF application had a remarkable influence on altering the physical and chemical properties of related product, leading to enhanced functionality (Juodeikiene et al., 2018). As such in Ates and Unal's paper (2023), gluten amount may probably have direct proportion with acrylamide quantity (Han et al., 2021). Because Han et al.…”
Section: Technologies For Reduction Of Acrylamidementioning
confidence: 95%
“…Because Han et al. (2021) suggested that, incorporating low‐gluten flour into the recipe, along with the assistance of IF phenomena during the deep‐frying process can have potential to prevent acrylamide formation.…”
Section: Technologies For Reduction Of Acrylamidementioning
confidence: 99%